2019
DOI: 10.1007/s10712-019-09550-y
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Sea Level Projections at the Coast by 2100

Abstract: As sea level is rising along many low-lying and densely populated coastal areas, affected communities are investing resources to assess and manage future socio-economic and ecological risks created by current and future sea level rise. Despite significant progress in the scientific understanding of the physical mechanisms contributing to sea level change, projections beyond 2050 remain highly uncertain. Here, we present recent developments in the probabilistic projections of coastal mean sea level rise by 2100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 118 publications
(224 reference statements)
0
49
0
1
Order By: Relevance
“…In other words, the LFCIV is an oceanic driver of coastal sea-level changes in the turbulent regime, which may compete with the external drivers examined in Woodworth et al (2019) and with the ocean-atmosphere coupled modes presented by Han et al (2019). More importantly, the random character of LFCIV suggests that it actually constitutes a source of uncertainty for the detection and attribution of coastal sea-level trends, in addition to those simulated by climate models (Carson et al 2019), and that these uncertainties should also be taken into account for coastal sea-level projections (see Jevrejeva et al 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In other words, the LFCIV is an oceanic driver of coastal sea-level changes in the turbulent regime, which may compete with the external drivers examined in Woodworth et al (2019) and with the ocean-atmosphere coupled modes presented by Han et al (2019). More importantly, the random character of LFCIV suggests that it actually constitutes a source of uncertainty for the detection and attribution of coastal sea-level trends, in addition to those simulated by climate models (Carson et al 2019), and that these uncertainties should also be taken into account for coastal sea-level projections (see Jevrejeva et al 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Section briefly reviews projections of future sea‐level change, highlighting key uncertainties that are relevant for decision making. More detailed reviews are available in several recent papers and assessment reports (e.g., Church et al, ; Clark et al, ; Oppenheimer et al, ; A. J. Garner et al, ; Horton et al, ; Jevrejeva et al, ; Slangen et al, ). Section examines the translation of future sea‐level change to extreme sea levels and related attempts to assess flooding on the current coastline.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that accounting for different physics in Antarctica can result in substantially different probabilistic projections of SLR by the end of the century (Jevrejeva et al, 2019;Kopp et al, 2019).…”
Section: Resultsmentioning
confidence: 99%